A two-phase ultrafine-grained NbMoTaWV refractory high entropy alloy with prominent compressive properties. (May 2022) - Peng, Haiyan; Kang, Zhixin; Long, Yan; Zhou, Li
Abstract: A NbMoTaWV high entropy alloy (HEA) was fabricated by mechanical alloying (MA) and spark plasma sintering (SPS). Characterization of milled powders indicated that only a single body-centered cubic (BCC) solid solution phase was generated in the MA process. After SPS, a tetragonal (Ta, V)O2 oxide phase precipitated from the primary BCC phase. The NbMoTaWV alloy exhibited a compressive yielding strength (σy ) of 2785 MPa, compressive strength (σmax ) of 3661 MPa and strain to failure (εf ) of 16.2% at room temperature. The compressive yielding strength of the sintered alloy was dramatically higher compared with most previously reported HEAs. The compressive strength of NbMoTaWV alloy at 1000 °C arrived at 1978 MPa. The excellent strength at room and elevated temperatures are mostly ascribed to the fine (Ta, V)O2 particles dispersed in the BCC matrix. Highlights: NbMoTaWV alloy with fine microstructure was fabricated by MA and SPS. (Ta, V)O2 particles were precipitated from BCC matrix during the SPS process. A combination of excellent strength and fair ductility was achieved in the HEA. The strength of the sintered HEA is much higher compared with most reported HEAs. (Ta, V)O2 particles improved the strength but reduced the ductility at 1000 °C.